Influence of motivation on teachers’ effectiveness in Ilorin West local government, Kwara State - Uyanne Elizabeth Obiageli; Omoshalewa Lasbat; Balogun Abdulrasaq Olatunji (Journal of Education and Learning (EduLearn), 2020)
Motivation is the vital tool that can enhance effectiveness and aid good performance. Individual job performance and behaviour depend greatly on motivational factors. A number of studies have been done in the area of motivation for teachers and its benefits towards better performance for the students. The purpose of this study was to investigate the influence of motivation on teachers’ effectiveness in Ilorin West Local Government Area, Kwara State. Adopted research design for this study was the descriptive survey method. The respondents comprises of 150 teachers which were simple randomly selected from 10 schools in Ilorin West. The instrument that was used for collecting data for this study was adopted from Ayuba (2017) titled Motivation and Teachers’ Effectiveness Questionnaire (MTEQ). Frequency count, percentage and mean score were used to answer research questions while Pearson Product Moment Coefficient (PPMC) and t-test were employed to test the research hypothesis. Findings revealed that teachers’ effectiveness is low and there was no significant influence of motivation on teachers’ effectiveness.